Analisa Aplikasi Keluhan Pelanggan Pada Pt Pln Ulp Medan Selatan Dengan Metode Servqual - Situmorang, Cathrin Desri Natalia; Sihaloho, Dumariana (Jurnal Kajian Ilmiah Teknologi Informasi dan Komputer, 2023)
PLN (Persero) is a state-owned organization owned by the majority of the public that has the capacity as a provider of electricity frameworks spread throughout Indonesia. The most common way to check customer complaints is by using the website in particular to provide information. Where this takes a few minutes to take care of customer complaints more quickly and accurately. So it can contribute with information to utilize websites that make information more coordinated with PCs which makes it easier to track information, process information, and report customer complaints quickly. This exploration provides an outline of the timeliness spent on filing customer complaints by utilizing a website-based framework. With this website-based framework, it will facilitate the process of inputting data for a more accurate information so that it can work in the most common way of finding and providing clearer information and all the data is more accurate, it can be formed according to customer wishes. One of the methods that can be used to measure customer complaints is the servqual method. This method makes a thorough evaluation of customer complaints,. The evaluation is completed in 5 components of administrative quality, namely: Tangibles (direct evidence), Reliability (reliability), Responsiveness (responsiveness), Assurance (assurance), Emphaty (attention). Customer dissatisfaction exists due to an imbalance between customer expectations and perceived service performance.